2011
DOI: 10.1093/rheumatology/ker379
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association study of NF-κB genes in UK Caucasian adult and juvenile onset idiopathic inflammatory myopathy

Abstract: Objective. Treatment-resistant muscle wasting is an increasingly recognized problem in idiopathic inflammatory myopathy (IIM). TNF-α is thought to induce muscle catabolism via activation of nuclear factor-kappa B (NF-κB). Several genes share homology with the NF-κB family of proteins. This study investigated the role of NF-κB-related genes in disease susceptibility in UK Caucasian IIM.Methods. Data from 362 IIM cases [274 adults, 49 (±14.0) years, 72% female; 88 juveniles, 6 (±3.6) years, 73% female) were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…This concept is supported by reports of family groups with IIM and according to those who develop the disease after exposure to environmental agents in certain geographical areas and during certain times of the year [12].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…This concept is supported by reports of family groups with IIM and according to those who develop the disease after exposure to environmental agents in certain geographical areas and during certain times of the year [12].…”
Section: Introductionmentioning
confidence: 66%
“…Some studies have described alleles of the ancestral HLA haplotype (HLA-A1~B8~DRB1*03:01 ~DQA*05:01) as risk factors for multiple autoimmune diseases, conferring very high possibilities of autoimmunity without being associated with specific diseases [12].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies were excluded because they contained no extractable data, other polymorphism data or review [23]–[34]. Finally, a total of eight published documents met our inclusion criteria [10][17](Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, MSA phenotypes and some clinical subgroups have distinct HLA risk and protective factors [21,22,26,88,94,162]. Through candidate gene studies, additional immune response genes have been identified as risk factors, including PTPN22 [135], STAT4 [89], NF-kappaB [27], pro-inflammatory cytokine polymorphisms of TNFa and IL-1a [115;140], immunoglobulin heavy chain phenotypes in JDM, dermatomyositis, and polymyositis, and NOTCH4 polymorphisms in IBM [95]. A genome-wide association study [15*] that combined specimens from several registries has confirmed the HLA region as strongest region of risk, but found additional autoimmune loci to be risk factors for dermatomyositis.…”
Section: Research Advances Through Myositis Registries and Biorepositmentioning
confidence: 99%